Oocyte aging in comparison to stem cells in mice - Nagamatsu, Go (Frontiers in Aging, 2023)
To maintain homeostasis, many tissues contain stem cells that can self-renew and differentiate. Based on these functions, stem cells can reconstitute the tissue even after injury. In reproductive organs, testes have spermatogonial stem cells that generate sperm in men throughout their lifetime. However, in the ovary, oocytes enter meiosis at the embryonic stage and maintain sustainable oogenesis in the absence of stem cells. After birth, oocytes are maintained in a dormant state in the primordial follicle, which is the most premature follicle in the ovary, and some are activated to form mature oocytes. Thus, regulation of dormancy and activation of primordial follicles is critical for a sustainable ovulatory cycle and is directly related to the female reproductive cycle. However, oocyte storage is insufficient to maintain a lifelong ovulation cycle. Therefore, the ovary is one of the earliest organs to be involved in aging. Although stem cells are capable of proliferation, they typically exhibit slow cycling or dormancy. Therefore, there are some supposed similarities with oocytes in primordial follicles, not only in their steady state but also during aging. This review aims to summarise the sustainability of oogenesis and aging phenotypes compared to tissue stem cells. Finally, it focuses on the recent breakthroughs in in vitro culture and discusses future prospects.